2022
DOI: 10.3389/fimmu.2022.880523
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and Their Small Extracellular Vesicles as Crucial Immunological Efficacy for Hepatic Diseases

Abstract: Mesenchymal stem cell small extracellular vesicles (MSC-sEVs) are a priority for researchers because of their role in tissue regeneration. sEVs act as paracrine factors and carry various cargos, revealing the state of the parent cells and contributing to cell–cell communication during both physiological and pathological circumstances. Hepatic diseases are mainly characterized by inflammatory cell infiltration and hepatocyte necrosis and fibrosis, bringing the focus onto immune regulation and other regulatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 154 publications
0
12
0
Order By: Relevance
“…A lot of studies have shown that sEVs possessed the anti-inflammation ability to polarize M1 macrophages to M2 macrophages which facilitated tissue regeneration [34][35][36][37][38][39][40][41][42][43][44][45][46]. However, the role of adipose tissue-derived small extracellular vesicles in modulating macrophage phenotypes and whether it was associated with soft tissue repair was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of studies have shown that sEVs possessed the anti-inflammation ability to polarize M1 macrophages to M2 macrophages which facilitated tissue regeneration [34][35][36][37][38][39][40][41][42][43][44][45][46]. However, the role of adipose tissue-derived small extracellular vesicles in modulating macrophage phenotypes and whether it was associated with soft tissue repair was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated macrophages played diverse functions, including scavenging debris ( Peng et al, 2007 ; Wynn and Vannella, 2016 ), recruiting host cells ( Wang et al, 2018 ), promoting vascularization ( Sun et al, 2017 ), and inducing cell differentiation ( Wang et al, 2017 ). Most previous studies focused on the anti-inflammation ability of sEVs to polarize M1 macrophages to M2 macrophages ( Kwak et al, 2022 ; Li et al, 2022 ; Liu et al, 2022 ; Tang et al, 2022 ; Yang et al, 2022 ; Zhao et al, 2022 ). However, the role of macrophages in cell recruitment was largely unknown, especially in the process of tissue regeneration induced by sEVs.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells also secret lncSNHG16 containing exosomes to influence other cells via lncSNHG16-TLR7 binding and MyD88/NF-κB/c-Myc activation. Since the exosomes derived from MSC and other cells are easily uptaken by NK cells and CD8 + T cells ( 117 ), it is reasonable to suspect that the exosomal lncSNHGs can influence the killer cell function via exosome-mediated intercellular communication.…”
Section: Lncsnhg-mediated Anti-tumor Immune Responsesmentioning
confidence: 99%